Developing inclusive mobile apps : building accessible apps for IOS and Android - Whitaker, Rob (Apress, 2020)
By failing to consider those with needs different to ourselves, we are telling these people they are not welcome in our app, and therefore that technology as a whole, is not for them. This is not hyperbole--23% of people in the US with a registered disability aren't online at all, that's three times more likely than the general population. When asked why they're not online, disabled respondents say their disability prevents them or that using the internet is too hard. To combat the issue of online exclusion, this book covers considerations mobile developers, or anyone creating mobile experiences, can use to make mobile work better for those with disabilities--mental or physical--and how to create a better experience for everyone. Software is not made up of cold, unthinking algorithms. Accessibility really plays down to your skills as a developer. Software is a craft in the truest sense of the word, and one of the greatest tools you can have as a craftsperson is empathy for the people who will be using your app. Each one of whom is an individual with different abilities, experiences, knowledge, and circumstances. You will: Create mobile experiences that work for as many people as possible Incorporate a worldview of accessibility and customer service into your design Work with accessibility tools and techniques commonly available for developers.